The Music Industries - Jones, M. author. aut Link
IX, 223 p.
Keywords: The music industry is undergoing immense change. This book argues that the transformations occurring across the various music industries - recording, live performance, publishing - can be characterised as much by continuity as by change, raising complex questions about the value of music commodities.